Antimicrobial Tear Lipids in the Ocular Surface Defense - Mudgil, Poonam (Frontiers in Cellular and Infection Microbiology, 2022)
The concept of antimicrobial lipids as effectors of innate host defense is an emerging field. There is limited knowledge on the antimicrobial role of lipids in the ocular environment. Tears act as first line of defense to protect the ocular surface from infections. Antimicrobial effects of tear lipids have been demonstrated using meibomian lipids that are the source of majority of lipids in tears. This article describes the knowledge available on the antimicrobial role of tear lipids at the ocular surface and the antimicrobial potential of various lipid classes present in tears that can contribute to antimicrobial protection of the eye. Like other mucosal secretions, tears contain many proteins and lipids with known antimicrobial effects. The antimicrobial defense of tears is far stronger than can be demonstrated by the effects of individual compounds many of which are present in low concentrations but synergistic and additive interactions between them provide substantial antimicrobial protection to the ocular surface. It is inferred that antimicrobial lipids play important role in innate defense of tears, and cooperative interactions between various antimicrobial lipids and proteins in tears provide a potent host defense mechanism that is effective against a broad spectrum of pathogens and renders self-sterilizing properties to tears for keeping the microbial load low at the ocular surface.